2017
DOI: 10.1093/mmy/myx003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 8-Hydroxyquinoline Derivatives as Hits for Antifungal Drug Design

Abstract: Clioquinol is an 8-hydroxyquinoline derivative that was widely used from the 1950s to 1970s as an oral antiparasitic agent. In 1970, the oral forms were withdrawn from the market due to reports of toxicity, but topical formulations for antifungal treatment remained available. Thus, the purpose of this study was to evaluate the toxicity, anti-Candida and antidermatophyte activity and to determine pharmacodynamic characteristics of clioquinol and other 8-hydroxyquinoline derivatives (8-hydroxy-5-quinolinesulfoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
5
44
0
Order By: Relevance
“…However, no substituent has led to the fungicidal activity for C. albicans . In this regard, our data were in agreement with previously reported in vitro results of the fungistatic and fungicidal activity of other 8‐hydroxyquinoline derivatives against C. albicans and dermatophytes, respectively (Pippi et al., ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, no substituent has led to the fungicidal activity for C. albicans . In this regard, our data were in agreement with previously reported in vitro results of the fungistatic and fungicidal activity of other 8‐hydroxyquinoline derivatives against C. albicans and dermatophytes, respectively (Pippi et al., ).…”
Section: Resultssupporting
confidence: 93%
“…Ear skin of pigs was used in this study. Procedures were performed according to our previous study (Pippi et al, 2017).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…So, time‐kill curves were used to obtain detailed information about the antifungal efficacy as a function of both time and concentration/association. Clioquinol, ciclopirox and terbinafine demonstrated fungicidal effect depending on the concentration and exposure time (Figure 1A) as well as previously reported by Pippi et al (2017), Kaur & Kakkar (2012) and Subisse et al (2010), respectively 16,37,38 …”
Section: Discussionsupporting
confidence: 88%
“…Current studies have shown that clioquinol inhibits effectively Candida spp. and dermatophytes with rare reports of resistance 16 …”
Section: Introductionmentioning
confidence: 99%
“…As a privileged scaffold, 8-hydroxyquinoline has been found in many natural products and drug candidates with remarkable biological and pharmaceutical activities. [1][2][3][4][5][6][7][8][9] Moreover, 8hydroxyquinolines have been gaining attention in metallocene complex catalyzed transformations, in which they are utilized as effective multidentate ligands. [10][11][12][13][14][15][16][17][18][19][20][21] In view of the remarkable importance of this class of heterocyclic compounds, the eld of 8-hydroxyquinoline synthesis is continuously gaining attention.…”
Section: Introductionmentioning
confidence: 99%